Challenging black people’s invisibility in the media of Brazil: possibilities in Critical Mathematics Education: possibilities in Critical Mathematics Education - Ramos de Britto, Reginaldo; Faustino, Ana Carolina (TANGRAM - Revista de Educação Matemática, 2025)
The articles aims to analyze the contribution of Mathematics Education to reading and writing situations that involve racism in the Brazilian media. To this end, we will discuss landscapes of investigation in which students were invited to analyze the (in)visibility of black people in Brazilian media. In the first landscape of investigation, entitled “Media and Racism,” the students of the final years of a public elementary school in Juiz de Fora, in Minas Gerais, Brazil, analyze the presence of black children in Brazilian magazines. In the second landscape of investigation, entitled “Billboards: analyzing issues of race and representation”, undergraduates in Education Research Degree analyze the presence of black and indigenous people in the billboards of a city in the state of Mato Grosso do Sul. This study shows that in the two investigated landscapes of investigations, the students identified the disproportionality between the percentage of black people in Brazil and thepercentage of their presence in magazines and billboards. The data also provide evidence that the landscapes of investigation have enabled students to use mathematics to identify situations of oppression and the fact that mathematics classrooms might constitute a place to challenge racism. At any educational level, the mathematics classroom could become a learning environment for the critical reading of different social practices, thus unveiling asymmetric processes and power relations established upon racial relations of the same nature.